Contemporary civil society in Nepal - Bhatta, C. D. (APISA, 2021)
In recent years, civil society has become the darling of economists, political scientists and policy makers both in the Western and non-Western world. The discourse on the modern concept of civil society in Nepal is fairly new despite the age-old existence of civic practices. But those civic practices of civil society were of a different kind, endowed with different responsibilities, and can hardly be equated with the current notion of civil society. That was a civil society with a limited civic sphere, engaged in indigenous activities which contributed little towards citizenship building. The reason for this was that the civic space was either pre-determined or restricted by the state due to a primitive political structure based on parochial thinking. This might be one of the reasons why civic resurgence did not emerge until political change irrupted in the nineties. The Third Wave of democratization that swept away undemocratic regimes worldwide in fact led to a worldwide growth of civil society. In most cases the wave itself was the repercussion of a worldwide civic resurrection that could not be contained within the borders of nation-states. (...)